Immunosuppressive therapy in liver transplantation: contribution to nursing - de Sá, Raphael Colares; Soares, Camilo Reuber de Sousa (Journal of Health Care, 2016)
Introduction: All patients undergoing liver transplantation require lifelong treatment with immunosuppressive agents in order to avoid graft rejection. Objective: This study aims to characterize the immunosuppressive therapy used in liver transplantation and propose nursing interventions to manage this therapeutic group. Method: This is a documental, bibliographical and descriptive research conducted from clinical protocols of liver transplantation from the transplant centers of Ceará, Brazil. From the protocols, the immunosuppressive agents used in liver transplantation were identified and then characterized about its clinical and pharmacological characteristics from the specialized and current literature in the field of medicine and pharmacology. It then proceeded with the discussion about the proper management of this therapy by the nursing team from the evidences of Micromedex and UpToDate bases. Results: Immunosuppressive agents have specific characteristics related to their indications, mechanisms of action, adverse effects and drug interactions, in which knowing and understanding these characteristics are fundamental to the management of the therapy aiming to an adequate graft function. In this scenario, the nursing team has responsibility not only in the administration of immunosuppressive agents, but also in monitoring the results, preventing complications and promoting health education for patients and families. Conclusions: The management of immunosuppressive agents requires nursing professionals scientifically grounded about the characteristics and related care in order to ensure a safe and effective therapy, as in to support the patient with relevant guidelines, thus ensuring their empowerment in the process of self-care.